Assessment of Health education which is provided to Postoperative Patients with Gallstone "Obstructive Jaundice" - Mohammed, widad; mohammed, Shatha (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A description study was carried through out the present study aimed to assess health education provided by nurses to patient with gall stone "obstructive jaundice". The study was conducted at 4 teaching hospital, Baghdad teaching hospital, Al-Karama teaching hospital, Al-Yarmook teaching hospital, Al-Kendy teaching hospital where choloecystectomy was performed, in the period from first of June 2004 to end of July 2004. Data were collected through the use of questionnaire an interview from which was developed for the purpose of the present study. A non-probability (purposive) sample which was consisted of (50) nurse who were dealing with patients who had choloecystectomy. The main result of the study revealed significant association between nurse’s gender, education level and their providing of health education about gall stone "obstructive jaundice" to the patients